On model based seasonal adjustment procedures - Jörg Breitung (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
In this note the unobserved component approach underlying the software package SEATS is compared with the Beveridge-Nelson type of decomposition for seasonal time series. The main strength of the SEATS approach lies in the appealing model formulation and the careful specification and adjustment of the input series. However, there are some theoretical problems with orthogonal decompositions which may be avoided by using the Beveridge-Nelson approach. The German unemployment series is studied to illustrate the properties of the alternative methods practically.
urn:nbn:de:kobv:11-10056467
Keywords: 330